Preparation method of modified fiber sponge based on electrostatic spinning

By mixing the polymer with gelatin and electrospinning, combining the steps of shearing, swelling, lyophilization and chemical crosslinking, the problem of insufficient mechanical properties and biocompatibility of the existing electrospinning fiber membranes was solved, and a modified fiber sponge with high shape restoration and good biocompatibility was prepared.

CN119746174APending Publication Date: 2025-04-04西安蝾螈生物技术有限公司

Patent Information

Application Number
CN202411973642.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing electrospun fiber membranes have shortcomings in mechanical properties and biocompatibility, and thermal crosslinking may lead to poor shape recovery and reduced biocompatibility.

Method used

After mixing the polymer with gelatin to form a viscous liquid, the fiber membrane is prepared by electrospinning, and it is sheared, swelled, lyophilized and chemically crosslinked to form a modified fiber sponge. This method overcomes the problems of insufficient mechanical properties and poor water absorption of the two-dimensional fiber membrane, and improves the stability of the fiber sponge through glutaraldehyde cross-linking.

Benefits of technology

The prepared electrospinned modified fiber sponge has high shape restoration, good biocompatibility and mechanical properties, which can effectively block the growth of non-osteoblasts while allowing the attachment and growth of fibroblasts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005219965970000081
    Figure BDA0005219965970000081
  • Figure BDA0005219965970000091
    Figure BDA0005219965970000091
  • Figure BDA0005219965970000101
    Figure BDA0005219965970000101
Patent Text Reader

Abstract

The invention provides a preparation method of modified fiber sponge based on electrostatic spinning, which comprises the following steps: firstly, mixing a polymer and gelatin, dissolving in a first organic solvent to prepare a spinning solution, stirring until a viscous liquid is formed, and preparing the viscous liquid into an electrostatic spinning fiber membrane by an electrostatic spinning method; cutting the electrostatic spinning fiber membrane into pieces, soaking the electrostatic spinning fiber membrane in a second organic solvent to swell the electrostatic spinning fiber membrane, smashing the electrostatic spinning fiber membrane by a high-speed homogenizer to obtain dispersion liquid, and filling the dispersion liquid in a cell culture plate for freeze-drying and shaping to obtain non-crosslinked short fibers; and carrying out chemical crosslinking on the short fibers by using a glutaraldehyde solution to stabilize the characters, washing with deionized water, sterilizing, and carrying out vacuum drying. The electrostatic spinning modified fiber sponge has excellent sealing performance and relatively high porosity and stability. And good biocompatibility and safety are achieved. Mechanical performance is good, water absorption is high, and longitudinal growth of cells is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to a preparation method of a modified fiber sponge based on electrostatic spinning. Background Art

[0002] Chronic periodontitis is a chronic inflammatory disease that occurs in the supporting tissues around teeth, with the main manifestations being gingival inflammation, periodontal pocket formation, alveolar bone resorption, and loose and displaced teeth. The basic purpose of periodontal treatment is to prevent further damage to periodontal tissues and to repair or regenerate damaged tissues. In recent years, guided tissue regeneration technology has been widely used in clinical practice to achieve periodontal tissue reconstruction through flap debridement and the use of barrier membranes and transplant materials.

[0003] Guided tissue regeneration (GTR) has been one of the hot topics in periodontal research over the past two decades. Its basic principle is to use a barrier membrane to prevent the root-oriented growth of the gingival epithelium and prevent the gingival connective tissue cells from contacting the root surface, maintaining a certain space so that periodontal ligament cells occupy the root surface, differentiate and proliferate to form new periodontal attachments. GTR technology has been proven to be able to achieve different degrees of tissue regeneration in both humans and animals. It has been used to treat periodontitis since the 1880s and has achieved good clinical results.

[0004] The ideal GTR membrane material should have the following conditions: good biocompatibility, good cell sealing, barrier properties to cells to allow nutrients to pass through, ability to generate and maintain regeneration space, good clinical operability, etc. With the development of the concept of tissue engineering, GTR membranes are also constantly improving. They are no longer limited to being used as barrier membranes, but are developing in the direction of inducing tissue regeneration / inducing bone regeneration. This requires GTR membranes to have certain biological functionality to improve the regeneration efficiency of alveolar bone tissue. Therefore, it is crucial to construct a biomembrane that can inhibit periodontal inflammatory response, promote osteogenic / angiogenic differentiation of periodontal ligament stem cells, and have good mechanical properties and controllable degradation rate for periodontal regeneration treatment.

[0005] The early concept of electrospinning was proposed by Anton Formhals in the 1930s. The electrospinning device consists of a high-voltage power supply, an injection device, and a collector. Electrospinning nanofibers can be customized according to specific requirements, are low-cost, can simulate extracellular matrix, promote cell proliferation and differentiation, and have good mechanical properties, biocompatibility, and anti-degradation capabilities. As scaffold materials, they have been widely used in tissue engineering such as bone, cartilage, and skin. However, the stacking method of electrospun fibers determines that even after the solvent evaporates, there will still be a small amount of residue on the membrane. The requirements for wire diameter, pore size, and porosity make electrospinning inefficient, high industrialization costs, soft fiber membranes, and poor mechanical properties. The method of modifying the fiber membrane into a fiber sponge can not only retain the characteristics of the electrospinning membrane itself, but also improve its mechanical strength.

[0006] CN114681678B provides a nanofiber sponge and a preparation method thereof, wherein an absorbable sponge-like wound dressing having a double-layer structure is prepared by spinning, swelling, freeze drying, soaking, glutaraldehyde cross-linking, etc. The polymer and collagen are in a tightly arranged aggregation state in the nanofiber, so that the active functional groups are less exposed, which seriously hinders the cross-linking effect of the cross-linking agent and the fiber, resulting in poor cross-linking effect and poor shape recovery.

[0007] CN109395146A proposes to use electrostatic spinning to obtain a mPEG-PCL nanofiber membrane, and the mPEG-PCL nanofiber membrane is homogenized, dispersed, freeze-dried and heat-treated to obtain a biomimetic scaffold material. CN118542962A dissolves cellulose acetate in an organic solvent to obtain an electrostatic spinning precursor solution, mixes drug-loaded inorganic particles, citric acid and polyvinyl alcohol solution to obtain an electrostatic spray solution, and obtains a drug-loaded inorganic particle composite fiber sponge by electrostatic spinning and thermal crosslinking. The limitations of these two methods are that although thermal crosslinking improves its anti-degradation ability and mechanical properties, it may cause thermal denaturation, resulting in poor shape recovery and reduced material biocompatibility. Summary of the invention

[0008] The object of the present invention is to provide a fiber sponge with high shape recovery and little influence of thermal denaturation and high biocompatibility.

[0009] To achieve the above purpose, the present invention provides a method for preparing a modified fiber sponge based on electrospinning, the special feature of which is that:

[0010] First, the polymer and gelatin are mixed in a mass ratio of 1:1 to 1:4, dissolved in a first organic solvent under continuous stirring, shaken and evenly mixed to form a spinning solution with a mass volume ratio of 5% to 30%, stirred to form a viscous liquid, vacuum degassed at 25° C. to 40° C., and the viscous liquid is prepared into an electrospinning fiber membrane by an electrospinning method;

[0011] Secondly, the electrospun fiber membrane is cut into pieces, immersed in 2% to 20% of the second organic solvent to make it swell, and broken by a high-speed homogenizer at a speed of 9000 to 10000 r / min for 10 to 15 minutes to obtain a dispersion, and the dispersion is placed in a cell culture plate, freeze-dried and shaped at -23°C to -80°C for 8 to 24 hours to obtain uncross-linked short fibers;

[0012] Finally, the uncrosslinked short fibers were chemically crosslinked using a glutaraldehyde solution prepared by mixing 25% glutaraldehyde and anhydrous ethanol in a volume ratio of 1:3 to 1:4 to stabilize the properties of the scaffold, and then rinsed with deionized water, sterilized, and vacuum dried for 8 hours to obtain an electrospun modified fiber sponge.

[0013] Further, the polymer is any one of polylactic acid, polyvinyl alcohol, polyurethane, polyamide, and polylactic acid-glycolic acid copolymer;

[0014] The first organic solvent is a mixture of any one or more of hexafluoroisopropanol, dichloromethane, 1,4-dioxane, N,N-dimethylformamide, chloroform, and tetrahydrofuran;

[0015] The second organic solvent is a mixture of any one or more of tert-butyl alcohol, methanol, isopropanol and ethanol;

[0016] The gelatin is any one of pig skin gelatin, fish skin gelatin, type I collagen, type II collagen, and type III collagen.

[0017] Furthermore, a flat receiver is used for receiving, a 15G-25G flat-head needle, the spinning parameters are a voltage of 10-25kv, a flow rate of 5-10ml / h, a receiving distance of 10-30cm, an ambient relative humidity of 40%-80%, an ambient temperature of 18°C-30°C, and a syringe of 10ml or more.

[0018] Furthermore, the electrospun modified fiber sponge has the following characteristics: polymer molecular weight is 20,000 to 300,000; molecular weight distribution is less than or equal to 3.0; membrane thickness is 0.25 to 0.75 mm, pore size is not greater than 50 μm, tensile strength should be greater than or equal to 7 MPa, and tear force is greater than or equal to 20N.

[0019] The beneficial effects of the present invention are:

[0020] The prepared electrospinning modified fiber sponge has the following advantages:

[0021] 1. It has excellent sealing properties, which not only effectively solves the shortcomings of the titanium mesh in barrier function and the problem of secondary removal, but also overcomes the problem of poor mechanical properties of the collagen membrane and easy to cause various inflammations.

[0022] 2. It has a high porosity, providing a large number of channels for material exchange. The three-dimensional structure of the short fibers is stabilized by chemical cross-linking. The short fibers are chemically cross-linked with glutaraldehyde to improve the stability of the fiber sponge. The biocompatibility and safety of the electrospinning modified fiber sponge have been proven by cytotoxicity tests and acute oral toxicity tests.

[0023] 3. The two-dimensional membrane produced by electrospinning is cut into pieces, homogeneously swollen, freeze-dried and chemically cross-linked, which overcomes the defects of existing two-dimensional fiber membranes such as insufficient mechanical properties, poor water absorption and limited longitudinal cell growth.

[0024] 4. The unique three-dimensional gradient microporous structure not only has good permeability, but also can block the growth of non-osteoblasts into the bone grafting area, while allowing the attachment and growth of fibroblasts. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a detail of the electrospun modified fiber sponge.

[0026] Figure 2 This is an electron microscope image of electrospinning modified fiber sponge. DETAILED DESCRIPTION

[0027] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose, the specific implementation methods, structural features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and embodiments.

[0028] In order to obtain a fiber sponge with high biocompatibility, high nanofiber material content, high shape recovery, and little influence of thermal denaturation, this embodiment provides a preparation method of a fiber sponge modified by electrospinning, which mainly includes the following steps:

[0029] First, the polymer and gelatin are mixed in a mass ratio of 1:1 to 1:4, dissolved in a first organic solvent under continuous stirring, shaken and evenly mixed to form a basic spinning solution with a mass volume ratio of 5% to 30%, stirred to form a viscous liquid, vacuum degassed at 25°C to 40°C, and the viscous liquid was prepared into an electrospinning fiber membrane by an electrospinning method;

[0030] Secondly, the electrospun fiber membrane is cut into pieces, immersed in 2% to 20% of the second organic solvent to make it swell, and broken by a high-speed homogenizer at a speed of 9000 to 10000 r / min for 10 to 15 minutes to obtain a dispersion, and the dispersion is placed in a cell culture plate, freeze-dried and shaped at -23°C to -80°C for 8 to 24 hours to obtain uncross-linked short fibers;

[0031] Finally, the uncrosslinked short fibers were chemically crosslinked using a glutaraldehyde solution prepared by mixing 25% glutaraldehyde and anhydrous ethanol in a volume ratio of 1:3 to 1:4 to stabilize the properties of the scaffold. The fibers were then rinsed with deionized water, sterilized, and vacuum dried for 8 hours to obtain an electrospun modified fiber sponge.

[0032] The polymer mentioned is any one of polylactic acid, polyvinyl alcohol, polyurethane, polyamide, polylactic acid-glycolic acid copolymer; the first organic solvent is any one or more of hexafluoroisopropanol, dichloromethane, 1,4-dioxane, N,N-dimethylformamide, chloroform, tetrahydrofuran; the second organic solvent is any one or more of tert-butyl alcohol, methanol, isopropanol, ethanol;

[0033] The gelatin is any one of pig skin gelatin, fish skin gelatin, type I collagen, type II collagen, and type III collagen.

[0034] The electrospinning technology uses a flat receiver, a 15G to 25G flat-head needle, spinning parameters of voltage 10 to 25kv, flow 5 to 10ml / h, receiving distance 10 to 30cm, relative humidity 40% to 80%, ambient temperature 18℃ to 30℃, and a syringe size of or equal to 10ml.

[0035] The prepared electrospinning modified fiber sponge has the following characteristics: polymer molecular weight is 20000-300000; molecular weight distribution is less than or equal to 3.0; membrane thickness is 0.25-0.75mm, pore size is not greater than 50μm, tensile strength should be greater than or equal to 7MPa, and tear force is greater than or equal to 20N.

[0036] It is not difficult to see that the above method cuts the two-dimensional membrane made by electrospinning into pieces, homogenizes and swells, freeze-dries and shapes it, and chemically cross-links it, thus overcoming the defects of the existing two-dimensional fiber membrane, such as insufficient mechanical properties, poor water absorption (as shown in Table 1, it has good water absorption properties) and limited vertical cell growth. And as can be seen from Table 1, each embodiment has a high recovery. Figure 2 It can be seen that the unique three-dimensional gradient microporous structure of the prepared electrospun modified fiber sponge not only has good permeability, but also can block the growth of non-osteoblasts into the bone grafting area, while allowing the attachment and growth of fibroblasts.

[0037] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be noted that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0038] Embodiment 1:

[0039] S1. Preparation of electrospinning fiber membrane: dissolve polycaprolactone and gelatin in hexafluoroisopropanol at a mass ratio of 1:3 to prepare a spinning solution with a mass volume ratio of 10%; stir for 12 hours, and after completely dissolving into a milky white viscous liquid, vacuum degassing at 25°C for 25 minutes, and then electrospinning membrane by electrospinning: use a 10mL syringe and a 22G flat-head needle to extract the spinning solution and fix it on the injection pump; wrap aluminum foil on a roller 15cm away from the needle, set the parameters to 12kV voltage, 5mL / h flow rate, 40% relative humidity, and 28°C ambient temperature, and perform electrospinning to obtain a polycaprolactone / gelatin fiber membrane;

[0040] S2, crushing: cut the polycaprolactone / gelatin fiber membrane into pieces, soak it in 5% tert-butyl alcohol to make it swell, and use a high-speed homogenizer to crush it at a speed of 10000r / min. After 10min, a dispersion is obtained, and the dispersion is placed in a cell culture plate, freeze-dried and shaped at -80℃ for 12h to obtain uncross-linked short fibers;

[0041] S3. Cross-linking: The uncross-linked short fibers were chemically cross-linked using a glutaraldehyde solution prepared by mixing 25% glutaraldehyde and anhydrous ethanol in a volume ratio of 1:3 to stabilize the properties of the scaffold. The fibers were then rinsed with deionized water, sterilized, and vacuum dried for 8 hours to obtain a polycaprolactone / gelatin fiber sponge.

[0042] Embodiment 2:

[0043] S1, preparation of electrostatic spinning fiber membrane: polylactic acid and fish skin gelatin are dissolved in hexafluoroisopropanol at a mass ratio of 1:1, and a spinning solution with a concentration of 10% is prepared; overnight stirring, after being thoroughly dissolved into a viscous liquid, vacuum degassing is performed at 25°C for 30 minutes, and then electrospinning is performed by electrospinning: with a 10mL syringe and a 25G flat-head needle, after extracting the spinning solution, it is fixed on a syringe pump; aluminum foil is wound around a roller 20cm away from the flat-head needle, and parameters are set: voltage 20kV, flow 6mL / h, relative humidity is 60%, and ambient temperature is 30°C, and electrostatic spinning is performed to obtain polylactic acid / fish skin gelatin fiber membrane;

[0044] S2, crushing: cut the polylactic acid / fish skin gelatin fiber membrane into pieces, soak it in 10% methanol to make it swell, use a high-speed homogenizer to break it up, the speed is 9000r / min, and after 15min, a dispersion is obtained, which is divided into cell culture plates, and freeze-dried and shaped at -80°C for 12h to obtain uncrosslinked short fibers;

[0045] S3, cross-linking: using glutaraldehyde solution prepared by mixing 25% glutaraldehyde and anhydrous ethanol in a volume ratio of 1:4, the uncross-linked short fibers were chemically cross-linked to stabilize the properties of the scaffold, and then rinsed with deionized water, sterilized, and vacuum dried for 8 hours to obtain a polylactic acid / fish skin gelatin fiber sponge.

[0046] Embodiment 3:

[0047] S1. Preparation of electrospinning fiber membrane: dissolving polylactic acid-co-glycolic acid and pig skin gelatin in dichloromethane at a mass ratio of 1:3 to prepare a spinning solution with a concentration of 10%; stirring for 10 hours, after completely dissolving into a viscous liquid, vacuum degassing at 40°C for 30 minutes, and then electrospinning membrane by electrospinning: using a 10mL syringe and an 18G flat-head needle, extract the spinning solution and fix it on a syringe pump; wrap aluminum foil around a roller 25cm away from the needle, set the parameters to 25kV voltage, 8mL / h flow rate, 80% relative humidity, and 30°C ambient temperature, and perform electrospinning to obtain polylactic acid-co-glycolic acid / pig skin gelatin fiber membrane;

[0048] S2, crushing: cut the polylactic acid-co-glycolic acid copolymer / pigskin gelatin fiber membrane into pieces, soak it in 15% ethanol to make it swell, and use a high-speed homogenizer to crush it at a speed of 9000r / min. After 15 minutes, a dispersion is obtained, and the dispersion is divided into cell culture plates, freeze-dried and shaped at -80°C for 12 hours to obtain uncross-linked short fibers;

[0049] S3. Cross-linking: The uncross-linked short fibers were chemically cross-linked using a glutaraldehyde solution prepared by mixing 25% glutaraldehyde and anhydrous ethanol in a volume ratio of 1:4 to stabilize the properties of the scaffold. After rinsing with deionized water, the fibers were sterilized and vacuum dried for 8 hours to obtain a polylactic acid-glycolic acid copolymer / porcine collagen fiber sponge.

[0050] Finally, the obtained electrospinning modified fiber sponge (hereinafter referred to as fiber sponge) was subjected to the following tests:

[0051] Performance Testing

[0052] 1. Absorption rate

[0053] Weigh the initial mass of the fiber sponge m0 (g), then immerse the fiber sponge in deionized water or blood (anticoagulated whole blood) for 10 min until the liquid is completely absorbed. Record the mass of the fiber sponge after the liquid is completely absorbed as m1 (g). Calculate the liquid absorption rate (LAR) of the nanofiber sponge to water or blood according to the following formula:

[0054]

[0055] 2. Bulk density

[0056] It is calculated by measuring the bulk volume and weighing it.

[0057] 3. Recovery rate

[0058] Cut the sample into 10×10mm specimens, measure its thickness and record it as h0, apply a 2N force to the sample steadily for 5 minutes. After removing the force, record the thickness after an interval of 10 minutes and record it as h1, and calculate the shape recovery rate (SRR) of the sample:

[0059]

[0060] 4. Porosity

[0061] Using the capillary condensation phenomenon and the principle of volume equivalent substitution, a capillary condensation model is established under the assumption that the shape of the pore is cylindrical and tubular, and then the pore size distribution characteristics and pore volume of the sample are estimated. By measuring the condensed gas volume of the sample under different pressure conditions, its isothermal adsorption and desorption curves are drawn, and its pore volume and pore size distribution curves can be obtained through different theoretical methods, and then its porosity can be analyzed and calculated.

[0062] Table 1 Performance test table

[0063] Absorption rate Bulk density Recovery rate Porosity Example 1 56.72 times <![CDATA[41.23kg / m 3 ]]> 87.49% 99.75% Example 2 42.45 times <![CDATA[31.57kg / m 3 ]]> 79.27% 95.54% Example 3 54.02 times <![CDATA[39.25kg / m 3 ]]> 81.71% 98.34%

[0064] The following cytotoxicity test and acute oral toxicity test are used to evaluate the biocompatibility and safety of the electrospun modified fiber sponge prepared by the present invention.

[0065] Test 1: Cytotoxicity test

[0066] 1. Test samples: Examples 1, 2 and 3 of the present invention.

[0067] 2. Experimental method: Refer to the method specified in GB / T 16886.5 Biological evaluation of medical devices Part 5: In vitro cytotoxicity test for testing.

[0068] 3. Evaluation Criteria

[0069] Cytotoxicity was evaluated by qualitative and quantitative methods. The qualitative grading standards for cytotoxicity are shown in Table 2:

[0070] Table 2 Qualitative grading of cytotoxicity morphology

[0071]

[0072] According to the method in Table 2, a grade greater than 2 is considered to have a cytotoxic effect.

[0073] Quantitative evaluation: The relative cell survival rate was calculated, and a decrease in cell activity greater than 30% was considered to be cytotoxic.

[0074] 4. Experimental Results

[0075] After 24 hours of action, the experimental results are shown in Table 3:

[0076] Table 3 Cytotoxicity test results of Examples 1-3 of the present invention

[0077] Grouping Qualitative grading of cytotoxicity by morphology Relative cell survival rate Example 1 Level 0 99.7% Example 2 Level 0 99.2% Example 3 Level 0 99.5%

[0078] 5. Conclusion: Examples 1, 2 and 3 of the present invention are non-cytotoxic.

[0079] Test 2: Acute oral toxicity test

[0080] 1. Test samples: Examples 1, 2 and 3 of the present invention.

[0081] 2. Experimental animals: 18 mice, half of which were female, weighing 22.0-27.0 g.

[0082] 3. Experimental method: Refer to the method specified in GB / T16886.11 Biological evaluation of medical devices Part 11: Systemic toxicity test for testing.

[0083] 4. Evaluation Criteria

[0084] After oral administration of the extract, the clinical reactions of the mice were observed and recorded immediately, and the clinical reactions of the mice were observed and the body weights were recorded 4 hours, 24 hours, 48 ​​hours and 72 hours after exposure to the samples.

[0085] 5. Experimental Results

[0086] Under the experimental conditions, the animals in each test group showed normal breathing, muscle movement, cardiovascular symptoms, hand hair, gastrointestinal tract, skin, etc., and no toxic reactions were observed (see Table 4 for details). The weight changes of the animals in the test groups (see Table 5 for details).

[0087] Table 4 Acute oral toxicity test results

[0088] Grouping immediately 4h 24h 48h 72h Example 1 Normal performance Normal performance Normal performance Normal performance Normal performance Example 2 Normal performance Normal performance Normal performance Normal performance Normal performance Example 3 Normal performance Normal performance Normal performance Normal performance Normal performance

[0089] Table 5 Record of weight changes of animals in acute oral toxicity test (g)

[0090]

[0091]

[0092] Through the above experimental verification, it can be seen that the fiber sponge prepared by the present invention has the following characteristics:

[0093] 1. It has excellent sealing and high porosity, which not only effectively solves the deficiency of titanium mesh in barrier function and the problem of secondary removal, but also provides a large number of channels for material exchange.

[0094] 2. The two-dimensional membrane obtained by electrospinning is cut into pieces, homogenously swollen, freeze-dried and chemically cross-linked, which overcomes the defects of the existing two-dimensional fiber membrane, such as insufficient mechanical properties, poor water absorption and limited longitudinal cell growth. Homogeneous swelling can expose more active sites, make cross-linking more complete, and be more conducive to the formation of three-dimensional gradient microporous structure. The short fibers are chemically cross-linked with glutaraldehyde, which greatly improves the stability of the fiber sponge compared to thermal cross-linking, and retains the high shape recovery of the sponge. The biocompatibility and safety of the electrospinning modified fiber sponge were proved by cytotoxicity test and acute oral toxicity test.

[0095] 3. The unique three-dimensional gradient microporous structure not only has good permeability, but also can block the growth of non-osteoblasts into the bone grafting area, while allowing the attachment and growth of fibroblasts.

Claims

1. A method for preparing a modified fiber sponge based on electrospinning, characterized in that: First, a polymer and gelatin are mixed in a mass ratio of 1:1 to 1:4, dissolved in a first organic solvent under continuous stirring, shaken and evenly mixed to obtain a spinning solution with a mass volume ratio of 5% to 30%, stirred to form a viscous liquid, vacuum degassed at 25° C. to 40° C., and the viscous liquid is prepared into an electrospinning fiber membrane by an electrospinning method; Secondly, the electrospun fiber membrane is cut into pieces, immersed in 2% to 20% of the second organic solvent to make it swell, and broken by a high-speed homogenizer at a speed of 9000 to 10000 r / min for 10 to 15 minutes to obtain a dispersion, and the dispersion is placed in a cell culture plate, freeze-dried and shaped at -23°C to -80°C for 8 to 24 hours to obtain uncross-linked short fibers; Finally, the uncrosslinked short fibers were chemically crosslinked using a glutaraldehyde solution prepared by mixing 25% glutaraldehyde and anhydrous ethanol in a volume ratio of 1:3 to 1:4 to stabilize the properties of the scaffold. The fibers were then rinsed with deionized water, sterilized, and vacuum dried for 8 hours to obtain an electrospun modified fiber sponge.

2. The preparation method according to claim 1, characterized in that: The polymer is any one of polylactic acid, polyvinyl alcohol, polyurethane, polyamide, and polylactic acid-glycolic acid copolymer; The first organic solvent is a mixture of any one or more of hexafluoroisopropanol, dichloromethane, 1,4-dioxane, N,N-dimethylformamide, chloroform, and tetrahydrofuran; The second organic solvent is a mixture of any one or more of tert-butyl alcohol, methanol, isopropanol and ethanol; The gelatin is any one of pig skin gelatin, fish skin gelatin, type I collagen, type II collagen, and type III collagen.

3. The preparation method according to claim 2, characterized in that: It adopts a flat receiver, a 15G-25G flat-head needle, the spinning parameters are voltage 10-25kv, flow rate 5-10ml / h, receiving distance 10-30cm, environmental relative humidity 40%-80%, environmental temperature 18℃-30℃, and the syringe is large or equal to 10ml.

4. The preparation method according to claim 1, 2 or 3, characterized in that: The electrospinning modified fiber sponge has the following characteristics: polymer molecular weight is 20000-300000; molecular weight distribution is less than or equal to 3.0; membrane thickness is 0.25-0.75mm, pore size is not greater than 50μm, tensile strength should be greater than or equal to 7MPa, and tear force is greater than or equal to 20N.

5. The preparation method according to claim 3, characterized in that: The following steps are included: S1. Preparation of electrospinning fiber membrane: dissolve polycaprolactone and gelatin in hexafluoroisopropanol at a mass ratio of 1:3 to prepare a spinning solution with a mass volume ratio of 10%; stir for 12 hours, and after completely dissolving into a milky white viscous liquid, vacuum degassing at 25°C for 25 minutes, and then electrospinning membrane by electrospinning: use a 10mL syringe and a 22G flat-head needle to extract the spinning solution and fix it on the injection pump; wrap aluminum foil on a roller 15cm away from the needle, set the parameters to 12kV voltage, 5mL / h flow rate, 40% relative humidity, and 28°C ambient temperature, and perform electrospinning to obtain a polycaprolactone / gelatin fiber membrane; S2, crushing: cut the polycaprolactone / gelatin fiber membrane into pieces, soak it in 5% tert-butyl alcohol to make it swell, and use a high-speed homogenizer to crush it at a speed of 10000r / min. After 10min, a dispersion is obtained, and the dispersion is placed in a cell culture plate, freeze-dried and shaped at -80℃ for 12h to obtain uncross-linked short fibers; S3. Cross-linking: The uncross-linked short fibers were chemically cross-linked using a glutaraldehyde solution prepared by mixing 25% glutaraldehyde and anhydrous ethanol in a volume ratio of 1:3 to stabilize the properties of the scaffold. After rinsing with deionized water, the fibers were sterilized and vacuum dried for 8 hours to obtain a polycaprolactone / gelatin fiber sponge.

6. The preparation method according to claim 3, characterized in that: The following steps are included: S1, preparation of electrostatic spinning fiber membrane: polylactic acid and fish skin gelatin are dissolved in hexafluoroisopropanol at a mass ratio of 1:1, and a spinning solution with a concentration of 10% is prepared; overnight stirring, after being thoroughly dissolved into a viscous liquid, vacuum degassing is performed at 25°C for 30 minutes, and then electrospinning is performed by electrospinning: with a 10mL syringe and a 25G flat-head needle, after extracting the spinning solution, it is fixed on a syringe pump; aluminum foil is wound around a roller 20cm away from the flat-head needle, and parameters are set: voltage 20kV, flow 6mL / h, relative humidity is 60%, and ambient temperature is 30°C, and electrostatic spinning is performed to obtain polylactic acid / fish skin gelatin fiber membrane; S2, crushing: cut the polylactic acid / fish skin gelatin fiber membrane into pieces, soak it in 10% methanol to make it swell, use a high-speed homogenizer to break it up, the speed is 9000r / min, and after 15min, a dispersion is obtained, which is divided into cell culture plates, and freeze-dried and shaped at -80°C for 12h to obtain uncrosslinked short fibers; S3, cross-linking: using glutaraldehyde solution prepared by mixing 25% glutaraldehyde and anhydrous ethanol in a volume ratio of 1:4, the uncross-linked short fibers were chemically cross-linked to stabilize the properties of the scaffold, and then rinsed with deionized water, sterilized, and vacuum dried for 8 hours to obtain a polylactic acid / fish skin gelatin fiber sponge.

7. The preparation method according to claim 3, characterized in that: The following steps are included: S1. Preparation of electrospinning fiber membrane: dissolving polylactic acid-co-glycolic acid and pig skin gelatin in dichloromethane at a mass ratio of 1:3 to prepare a spinning solution with a concentration of 10%; stirring for 10 hours, after completely dissolving into a viscous liquid, vacuum degassing at 40°C for 30 minutes, and then electrospinning membrane by electrospinning: using a 10mL syringe and an 18G flat-head needle, extract the spinning solution and fix it on a syringe pump; wrap aluminum foil around a roller 25cm away from the needle, set the parameters to 25kV voltage, 8mL / h flow rate, 80% relative humidity, and 30°C ambient temperature, and perform electrospinning to obtain polylactic acid-co-glycolic acid / pig skin gelatin fiber membrane; S2, crushing: cut the polylactic acid-co-glycolic acid copolymer / pigskin gelatin fiber membrane into pieces, soak it in 15% ethanol to make it swell, and use a high-speed homogenizer to crush it at a speed of 9000r / min. After 15 minutes, a dispersion is obtained, and the dispersion is divided into cell culture plates, freeze-dried and shaped at -80°C for 12 hours to obtain uncross-linked short fibers; S3. Cross-linking: The uncross-linked short fibers were chemically cross-linked using a glutaraldehyde solution prepared by mixing 25% glutaraldehyde and anhydrous ethanol in a volume ratio of 1:4 to stabilize the properties of the scaffold. After rinsing with deionized water, the fibers were sterilized and vacuum dried for 8 hours to obtain a polylactic acid-glycolic acid copolymer / porcine collagen fiber sponge.

Citation Information

Patent Citations

  • Preparation method for nanofiber porous scaffold having compression elasticity in wet state

    CN105107022A

  • Preparation method of electrospinning fiber scaffold material

    CN110975009A

  • Organic / inorganic composite three-dimensional porous nanofiber tissue engineering scaffold as well as preparation method and application thereof

    CN114870070A

Cited By

  • Asymmetric short fiber aerogel stent loaded with magnesium oxide as well as preparation method and application of asymmetric short fiber aerogel stent

    CN120754304A